Effective support following recurrent pregnancy loss: a randomized controlled feasibility and acceptability study. Issue 5 (May 2020) - Bailey, Sarah; Boivin, Jacky; Cheong, Ying; Bailey, Christopher; Kitson-Reynolds, Ellen; Macklon, Nick
Abstract: Research question: Is it feasible to perform a future definitive trial to determine the effectiveness of the positive reappraisal coping intervention (PRCI) in improving the psychological well-being of women with recurrent pregnancy loss (RPL) during the early stages of a new pregnancy? Design: This mixed method study aimed to establish the feasibility of conducting a multicentre randomized controlled trial (RCT) to definitively test the effects of the PRCI on the psychological well-being of women with RPL. Participants ( n  = 75) were recruited to the study and at the point of a positive pregnancy test, 47 were randomized into two study groups. The intervention group received the PRCI and weekly questionnaire assessment (Hospital Anxiety and Depression Scale and Weekly Record Keeping Form [WRK]) to monitor psychological well-being; the control group received the same questionnaires. Nested within the RCT was a qualitative process evaluation (QPE) exploring participants' subjective experience of study methods and the intervention. The study was conducted over a two-year period between 2014 and 2016. Results: This study successfully gathered knowledge about the feasibility aspects of conducting a future multicentre definitive study to determine the effects of the PRCI on the psychological well-being of women with RPL. Participants were receptive to its use and the intervention appeared to convey benefits with no apparent downside. Conclusions: The study concluded that a definitive RCT of the PRCI is possible and that the model of care already has the potential to be made more widely available as a safe, low-cost, convenient and easily deliverable intervention to provide much-needed support to a vulnerable patient population.